PI5P4Kα supports prostate cancer metabolism and exposes a survival vulnerability during androgen receptor inhibition - Triscott, Joanna; Reist, Matthias; Küng, Lukas; Moselle, Francielle C. [UNESP]; Lehner, Marika; Gallon, John; Ravi, Archna; Arora, Gurpreet K.; De Brot, Simone; Lundquist, Mark; Gallart-Ayala, Hector; Ivanisevic, Julijana; et al. (American Association for the Advancement of Science (AAAS), 2023)
Phosphatidylinositol (PI)regulating enzymes are frequently altered in cancer and have become a focus for drug development. Here, we explore the phosphatidylinositol-5-phosphate 4-kinases (PI5P4K), a family of lipid kinases that regulate pools of intracellular PI, and demonstrate that the PI5P4Kα isoform influences androgen receptor (AR) signaling, which supports prostate cancer (PCa) cell survival. The regulation of PI becomes increasingly important in the setting of metabolic stress adaptation of PCa during androgen deprivation (AD), as we show that AD influences PI abundance and enhances intracellular pools of PI-4,5-P2. We suggest that this PI5P4Kα-AR relationship is mitigated through mTORC1 dysregulation and show that PI5P4Kα colocalizes to the lysosome, the intracellular site of mTORC1 complex activation. Notably, this relationship becomes prominent in mouse prostate tissue following surgical castration. Finally, multiple PCa cell models demonstrate marked survival vulnerability following stable PI5P4Kα inhibition. These results nominate PI5P4Kα as a target to disrupt PCa metabolic adaptation to castrate resistance.